2015
DOI: 10.5539/ijps.v7n3p76
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Target Repetition on Semantic Priming in a Three-Target RSVP Task

Abstract: This study used a rapid serial visual presentation task to examine the impact of target relatedness on report accuracy. In this task participants were shown a series of briefly presented words and were required to identify the three colored target words from the stream of distractor words. In two experiments participants either recalled the three targets words from memory at the end of each trial or recognized the targets from a list of all possible targets. The first target shown on each trial was unrelated t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…However, this theoretical consensus may be unwarranted. In contradiction with the postperceptual account, several behavioral studies showed that semantic priming from blinked items is either severely reduced or entirely eliminated (e.g., Martens et al, 2002;Murphy & Bloom, 2015;Zivony & Lamy, 2016). These findings raise the possibility that although semantic processing may occur during the blink, it is weakened to the extent that it may have little effect on downstream processes.…”
Section: Selective Theoretical Overviewmentioning
confidence: 91%
See 1 more Smart Citation
“…However, this theoretical consensus may be unwarranted. In contradiction with the postperceptual account, several behavioral studies showed that semantic priming from blinked items is either severely reduced or entirely eliminated (e.g., Martens et al, 2002;Murphy & Bloom, 2015;Zivony & Lamy, 2016). These findings raise the possibility that although semantic processing may occur during the blink, it is weakened to the extent that it may have little effect on downstream processes.…”
Section: Selective Theoretical Overviewmentioning
confidence: 91%
“…The findings from N400 studies reviewed here show that semantic processing is most often disrupted during the blink period (Batterink et al, 2010;Giesbrecht et al 2007;Peressotti et al, 2012;Pesciarelli et al, 2007;Rolke et al, 2001;Weller et al, 2018). Considering that many behavioral studies demonstrated that semantic priming is also reduced (e.g., Martens et al, 2002;Murphy & Bloom, 2015;Zivony & Lamy, 2016), it is surprising that the post-perceptual account of the AB was so widely embraced. This state of affairs is likely to result from the implicit assumption that at any given moment, semantic information is either fully represented or not at all, and accordingly, that it should be either unaffected or entirely suppressed by the blink.…”
Section: Disrupted Engagement and Semantic Processing During The Blinkmentioning
confidence: 99%
“…However, this theoretical consensus may be unwarranted. In contradiction with the postperceptual account, several behavioral studies showed that semantic priming from blinked items is either severely reduced or entirely eliminated (e.g., Martens et al, 2002;Murphy & Bloom, 2015;Zivony & Lamy, 2016). These findings raise the possibility that although semantic processing may occur during the blink, it is weakened to the extent that it may have little effect on downstream processes.…”
Section: Selective Theoretical Overviewmentioning
confidence: 98%
“…The findings from N400 studies reviewed here show that semantic processing is most often disrupted during the blink period (Batterink et al, 2010;Giesbrecht et al 2007;Peressotti et al, 2012;Pesciarelli et al, 2007;Rolke et al, 2001;Weller et al, 2018). Considering that many behavioral studies demonstrated that semantic priming is also reduced (e.g., Martens et al, 2002;Murphy & Bloom, 2015;Zivony & Lamy, 2016), it is surprising that the post-perceptual account of the AB was so widely embraced. This state of affairs is likely to result from the implicit assumption that at any given moment, semantic information is either fully represented or not at all, and accordingly, that it should be either unaffected or entirely suppressed by the blink.…”
Section: Disrupted Engagement and Semantic Processing During The Blinkmentioning
confidence: 99%
“…Likewise, in many behavioral studies, semantic priming either was reduced (Martens, Wolters & van Raamsdonk, 2002; Zivony & Lamy, 2016) or disappeared altogether (Murphy & Bloom, 2015; Rolke et al, 2001; Peressotti et al, 2012) during the blink. For instance, Peressotti et al (2012) used the three-target paradigm developed by Shapiro et al (1997), in which three targets are presented in one stream.…”
Section: Introductionmentioning
confidence: 96%